Active Disturbance Rejection Control of Valve-Controlled Cylinder Servo Systems Based on MATLAB-AMESim Cosimulation. (11th September 2020) - Guo, Wenxiao; Zhao, Yanbin; Li, Ruiqin; Ding, Haigang; Zhang, Jianwei
Abstract : The valve-controlled cylinder position servo system has the advantages of large output force and large power. As characteristics of nonlinearity and uncertainty exist in the hydraulic servo system, it is difficult for the traditional PID control to meet the requirements of high precision and control. The active disturbance rejection control (ADRC) considers the uncertainty of the system and external disturbances as the total disturbance. In this paper, the valve-controlled cylinder servo system is designed based on ADRC, its working principle is described, and its mathematical model and cosimulation model based on MATLAB-AMESim are established. In the case of constant load, variable load, and long pipeline, the comparative simulation of ADRC and PID is carried out. The simulation results show that the ADRC can effectively suppress the disturbance of the internal parameter changes and external load changes of the hydraulic system and has strong robustness and high control accuracy. This study provides a reference for the application of ADRC in electrohydraulic servo systems.